Precision agriculture techniques for optimizing chemical fertilizer use and environmental sustainability: a systematic review - Cai, Baozhong; Shi, Fang; Geremew, Betelhem A.; Addis, Amsalu K.; Abate, Meseret C.; Dessie, Wubliker; Bayu, Tesfaye (Frontiers in Agronomy, 2025)
Precision agriculture (PA) techniques are critical for optimizing chemical fertilizer use in modern farming. However, a comprehensive synthesis of their effectiveness in enhancing nutrient management and reducing environmental impacts is lacking. This systematic review, following Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, analyzes global evidence to evaluate PA’s role in improving fertilizer application practices. Our analysis of 51 peer-reviewed studies reveals that PA significantly enhances nutrient use efficiency and crop yields. Specifically, 37.25% of studies highlight PA-driven technological innovations, while 29.41% document major improvements in nutrient management. These findings confirm that PA promotes sustainable fertilizer utilization and reduces environmental footprints. To realize its full benefits, policymakers must address key challenges to widespread adoption, such as cost barriers, lack of technical expertise, and infrastructure limitations.